Optimizing the Use of QRIS as an Alternative Payment Method for MSMEs in Bima City from an Islamic Economics Perspective - Masrin Maulana; Rafiuddin Rafiuddin; Dinah Husniah (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
The development of digital payment systems has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt the Quick Response Code Indonesian Standard (QRIS) as a more efficient transaction method. However, its implementation in developing areas such as Bima City still faces challenges, particularly related to digital literacy and social characteristics of the community. This study aims to analyze the optimization of QRIS usage among MSMEs and examine its compliance with Islamic economic principles. This research employs a qualitative approach with a descriptive field research design, where data are collected through observation, interviews, and documentation of MSME actors using QRIS. The results show that QRIS enhances transaction efficiency and convenience while supporting business competitiveness. However, its implementation is not yet optimal due to the dominance of cash transactions, low digital literacy, and usage disparities among age groups. From an Islamic economic perspective, QRIS usage aligns with the principles of riba-free transactions, clarity (gharar avoidance), honesty, and transparency. Nevertheless, these values are still applied practically rather than based on conceptual understanding. Therefore, efforts to improve digital literacy and strengthen awareness of Islamic economic values are needed to achieve an inclusive and equitable payment system.